Saúde mental e trabalho rural no processo de reestruturação produtiva de uma empresa do setor sucroalcooleiro em Minas Gerais - Brasil - Isabella Diniz Faria (2012)
Introduction: the productive restructuring phenomenon is being expressed in the rural environment with new ways of organization, relationships and work conditions. The objective of this study was to analyze the consequences of productive restructuring in the sugarcane/alcohol industry on the cane cutter workers mental health, on its current work process and its perspectives related to their future job. Methods: a case study with a qualitative approach was conducted, with six Focus Groups, composed from a 710 rural sugarcane workers of a sugarcane/alcohol industry in the state of Minas Gerais, Brazil. Each group had an average number of 12 participants. Results: on the workers speech, feelings like fear, loss, insecurity, concern, nervousness, personal devaluation and a drop of professional prestige were identified with the development of the mechanization of the cane harvest. Social impacts like drug abuse, increase in armed robbery, and violence were discussed as possible consequences of the mass unemployment of this workers. As coping traits to this possible situation, alternatives like looking for less hard rural work, opening their own business, retum to school and specialization courses were cited. Discussion: professional disqualification and changes on the job profile after harvest mechanization are recognized by the sugar cane workers, who tend to develop coping traits upon possible unemployment. Even with differences on the way each worker deal with this changing process, these changes are being source of mental suffering and treats to physical/psychological integrity. This way, a profotmd discussion about these workers' mental health is relevant, to build health suryeillance for the rural sugarcane workers.